NEW INDICATORS FOR PREDICTING THE SEVERITY OF ACUTE PANCREATITIS BASED ON DATA OBTAINED DURING LAPAROSCOPY - XUJABAEV Safarboy Tuxtabayevich; XOLIYEV Obidjon Odil o'g'li; DUSIYAROV Mukhammad Mukumbaevich (Scholar Express Journals, 2024)
102 patients with acute destructive pancreatitis complicated by fermentative peritonitis who underwent laparoscopy in the first 72 hours from the moment of the disease were treated. Based on the results of laparoscopy, a score of abdominal cavity pathologic changes in acute pancreatitis was developed, which allows predicting the severity of the disease course. The results of the point estimation of pathologic changes in the abdominal cavity at laparoscopy are comparable (sensitivity of the method is 86.3%) with the scale of acute pancreatitis severity according to the results of Balthazar computer tomography (91.2%).
Keywords: Acute pancreatitis; laparoscopy; choledocholithiasis and gallstone disease